Using a moored underwater video system to study the influence of environmental factors on coral reefs fish behaviour - Loiseau, Nicolas (2023)
The present study examined how environmental variables (sea surface temperature (SST), tide, wind velocity and direction, light intensity, and rainfall) influence the structure of coral fishes community around a small coral colony. An autonomous underwater video system fixed on the substrata was used to census fish around a coral colony. The diversity and abundance of fishes were recorded over four consecutive months, seven times per day from sunrise to sunset. A total of 73,880 fishes belonging to 92 species and 23 families were observed. The total number of species (S) and families observed per day, and per sequence, were not influenced by the environmental factors. Environmental variables had significant but weak effect on Serranidae, Haemulidae, Chaetodontidae, Labridae, Scaridae, Siganidae and Acanthuridae and have more important effect on 4 families (Lethrinidae, Lujtanidae, Pomacentridae and juvenile labridae). Up to 50% of the variability in the abundance of Lethrinidae was explained by 4 environmental factors: tide, wind direction, light intensity and sea temperature. Lutjanidae and Lethrinidae presented opposite patterns related to with wind direction and tide. At the species level, Chromis viridis (Pomacentridae) were significatively influenced by the light intensity. Our results reveal that tide and light intensity are key factors influencing the patterns of studies families.